Characteristic of Hydrothermal Alteration, Ore Mineralization And Fluid Inclusion Of Watuijo Prospect, Tulungagung Regency As An Indication Of Porphyry CU System - Dian Yesy Fatimah; Arifudin Idrus; I Wayan Warmada; Iwan Setiawan (JURNAL TEKNOLOGIA, 2020)
Watuijo Prospect is located in Panggunguni Village, Tulungagung district, East Java Province, Indonesia. The alteration rock, as a lithocap, is associated with stockwork veinlet which is filling by pyrite, malachite and azurite. The aim of this research is to characterize mineralization type using field data that analyzed by petrography, XRD, and fluid inclusion methods. The geology of research area was consist of sandstone and limestone as a wall rock that intruded by dacite as a host rock.. The hydrothermal alteration can be identified as phyllic alteration, argillic alteration and also advanced argillic alteration. Ore mineralization is characterized by disseminated sulphides such as pyrite, chalcopyrite, magnetite, bornite, sphalerite, covelite, and digenite with veinlet type are A type, AB type, and D type. Hydrothermal fluid of Watuijo Prospect is typified by high temperature (~385 to >400oC) and high salinity (46 to 52 wt.% NaCl). It shows that the type of the deposit is Cu-Au mineralization of porphyry system.